Association between interleukin‐19 and angiopoietin‐2 with vascular complications in type 2 diabetes. Issue 6 (24th April 2016) - Li, Li; ZHeng‐Qing, Yu; Juan‐Yu, Hu; Jian‐Yong, Xu; Fan, Liu; Guang‐Chun, Zhao; Lei, Zhang; Hui‐Ming, Gu; Si‐Jing, Zhang; Meng, Jin
Abstract: Aims/Introduction: The aim of the present study was to investigate the role of interleukin‐19 (IL‐19) in angiogenesis of type 2 diabetes mellitus with complications, and to assess the relationship of serum IL‐19 and angiopoietin‐2 (Ang‐2) in type 2 diabetes mellitus. Materials and Methods: The group studied comprised of 240 patients with type 2 diabetes mellitus (132 men and 108 women), and included macrovascular complications, microvascular complications and type 2 diabetes mellitus without vascular complications. The control group consisted of 50 healthy blood donors. All participants were evaluated for: IL‐19, Ang‐2, fasting plasma glucose, fasting insulin and glycosylated hemoglobin. Results: The serum IL‐19 levels of type 2 diabetes mellitus patients with angiopathy were found to be significantly higher compared with patients without angiopathy. IL‐19 levels were significantly positively correlated with Ang‐2, homeostasis model assessment for insulin resistance and glycosylated hemoglobin ( r = 0.769, 0.523 and 0.491, respectively, P < 0.01). In multivariable logistic regression analysis, IL‐19 levels ( P = 0.01) were found to be independently associated with patients with type 2 diabetes mellitus complications. Conclusions: These data are the first to implicate the association between the IL‐19 and type 2 diabetes mellitus with vascular complications. IL‐19 is significantly positively correlated with Ang‐2. The potential role of IL‐19 and Ang‐2 in the pathogenesis of vascular complications in type 2 diabetes could warrant further study. Abstract : Serum IL‐19 and Ang‐2 were significantly elevated in patients with T2DM. Specifically, they were positive correlated with the numbers of vascular complications of T2DM. IL‐19 is positively correlated with Ang‐2. IL‐19 and Ang‐2 may be involved in angiogenesis of T2DM with vascular complications.